'He Went Down to Joppa and Found a Ship Going to Tarshish' (Jonah 1:3): Landscape Reconstruction at Jaffa and a Potential Early Harbour. (3rd July 2022) - Wachsmann, Shelley; Burke, Aaron A.; Dunn, Richard K.; Avnaim-Katav, Simona
ABSTRACT: Recent excavations of Tel Yafo (Jaffa), Israel, underscore its role as an historically important Mediterranean port. In 2014, the Ioppa Maritima Project conducted a geological investigation determining that from ca. 5000–2000 years BP, a small estuarine system existed east and north of Tel Yafo that could have served as a harbour. The marine re-entrant formed through sea-level rise and flooding of a small valley, and the stream mouth was probably also partially blocked by coastal sands. Sediment aggradation, wetland development, and anthropogenic activity largely filled the embayment leaving only a depression east of Tel Yafo in the area of Bloomfield Stadium and Groningen Park.